VFA And Ammonia Emission During Separate Collection Of Residential Waste As A Measure Of Odour Potential - N. Qamaruz-Zaman, N. Qamaruz-Zaman; M.W. Milke, M.W. Milke (2011)

(untitled)
The separate collection and transportation of food residues from residential waste, saves landfill capacity, but presents with it the issue of malodour (Qamaruz-Zaman and Milke, 2008).